The Impact of Green Innovation, Green Intellectual Capital, and Company Size To Financial Performance - Yucha, Nikma (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
This research aims to analyze green innovation, green intellectual capital, and company size on the financial performance of manufacturing companies in 2020-2023. The research method is quantitative research using multiple linear regression analysis tools. The sample used was 33 companies with purposive sampling techniques. The research results show that the variables green innovation and green intellectual capital do not have a significant effect on financial performance, while the variable company size has a significant positive effect on financial performance.